The Bladder Tumor Suppressor Protein TERE1 (UBIAD1)Modulates Cell Cholesterol: Implications for Tumor Progression - Fredericks, William J. (Mary Ann Liebert, Inc., 2011)
Convergent evidence implicates the TERE1 protein in human bladder tumor progression and lipid metabolism. Previously, reduced TERE1 expression was found in invasive urologic cancers and inhibited cell growth upon re-expression. A role in lipid metabolism was suggested by TERE1 binding to APOE, a cholesterol carrier, and to TBL2, a candidate protein in triglyceride disorders. Natural TERE1 mutations associate with Schnyder's corneal dystrophy, characterized by lipid accumulation. TERE1 catalyzes menaquinone synthesis, known to affect cholesterol homeostasis. To explore this relationship, we altered TERE1 and TBL2 dosage via ectopic expression and interfering RNA and measured cholesterol by Amplex red. Protein interactions of wild-type and mutant TERE1 with GST-APOE were evaluated by binding assays and molecular modeling. We conducted a bladder tumor microarray TERE1 expression analysis and assayed tumorigenicity of J82 cells ectopically expressing TERE1. TERE1 expression was reduced in a third of invasive specimens. Ectopic TERE1 expression in J82 bladder cancer cells dramatically inhibited nude mouse tumorigenesis. TERE1 and TBL2 proteins inversely modulated cellular cholesterol in HEK293 and bladder cancer cells from 20% to 50%. TERE1 point mutations affected APOE interactions, and resulted in cholesterol levels that differed from wild type. Elevated tumor cell cholesterol is known to affect apoptosis and growth signaling; thus, loss of TERE1 in invasive bladder cancer may represent a defect in menaquinone-mediated cholesterol homeostasis that contributes to progression.